DAMPAK ARUS DIGITALISASI TERHADAP PERUBAHAN POLA INTERAKSI SOSIAL SISWA SEKOLAH DASAR - Istiqomah, Siti Nur; Farisha Dea Nurapriliyani; Qorina Ammara; Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digitalization has significantly influenced the lives of elementary school students, particularly in shaping their social interaction patterns. The increasing use of digital devices potentially affects how students communicate and interact within their social environment. This study aims to describe the impact of digitalization on changes in social interaction patterns among elementary school students. A descriptive qualitative approach was employed, and the study was conducted at SD Negeri 1 Kedawung,Cirebon Regency .The research consisted of 26 sixth-grade students ,one classroom teacher, and two parents. Data were collected through observations and semi-structured interviews and analyzed using data reduction, data display and conclusion drawing with source and triangulation. The findings indicate that digitalization has led to a decrease in direct social interactions, a increase in individualistic behavior, and decline in students verbal communication ,particularly outside classroom activities. Although digital technology supporting learning processes, uncontrolled use may negatively affect the quality of students ‘social interaction. Therefore, the active involvement of teachers and parents is essential to guide the appropriate use of digital technology to support students ‘social development .